Radiofrequency catheter ablation in pediatric population: clinical, electrophysiological and therapeutic characteristics in a Peruvian pediatric hospital - Melgar Quicaño, Luis Alfredo (2021)
Objective. This study aims to describe the clinical, electrophysiological and therapeutic characteristics of pediatric patients with supraventricular tachycardia undergoing radiofrequency ablation. Materials and methods. Observational, descriptive, retrospective study of children admitted for supraventricular tachycardia treatment at the Instituto Nacional de Salud del Niño during 2018 to 2021. Results. Data from 62 procedures were collected, corresponding to 59 patients (mean age: 9.91 years, 61% male), 23% of procedures were performed in patients under 15kg, and two were in patients under 5kg. 63% of patients had a structurally normal heart, while 37% had some type of congenital heart disease, the most common being Ebstein’s anomaly. The most widely used group of drugs were beta-blockers, mainly propranolol. Among the arrhythmias treated, 21.7% had preexcitation Syndrome, 33.3% had at least one hidden accessory pathway, 5% corresponded to permanent reciprocating junctional tachycardia, 5% intranodal tachycardia, 11.7% atrial tachycardia, 10 % atrial flutter, 5% had other types of tachycardia and in 5 cases no tachycardia was induced. Of the total procedures, 76% corresponded to electrophysiological study and ablation, four patients recurred. Conclusions. The most common supraventricular tachycardia substrate in children was the presence of some accessory pathway. Radiofrequency catheter ablation could be applied in children with a high success rate and a low complication rate.